Peran Badan Perwakilan Desa (BPD) Dalam Mewujudkan Demokrasi Desa di Desa Buangin Kecamatan Towuti Kabupaten Luwu Timur - Darwis, Muh.; Sabri, Muh. (Program Studi Hukum Tata Negara (Siyasah) IAIN Palopo, 2020)
Â AbstractDeliberative Village functions to accommodate and the aspirations channel of the community, and together with the Head establish Village regulations, the role of the Village Consultative Body was very important, The Village regulations established was truly regulations that originate from the aspirations of the community. The role of the Village Consultative Body in implementing the establishment of Village regulations in Buangin Village, Towuti Subdistrict, East Luwu Regency, not all villages was in accordance with RI Law Number 32 of 2004 concerning Regional Government and Government Regulation Number 72 of 2005 concerning Villages. Even though there has been a new Law, namely Law No. 6 of 2014 concerning Villages, and government regulation no. 43 of 2014 Middle Village. This discrepancy was influenced by several factors, namely factors of education, employment, and experience in office.AbstrakBadan Permusyaratan Desa berfungsi untuk menampung dan menyalurkan aspirasi masyarakat, serta bersama-sama Kepala Desa menetapkan peraturan Desa, makaÂ peran Badan Permusyawaratan Desa sangat penting, agarÂ peraturan Desa yang ditetapkan benar-benar merupakan peraturan yang bersumber aspirasi masyarakat. Peran Badan Permusyawaratan Desa dalam pelaksanaan pembentuka peraturan Desa di Desa Buangin Kecamatan Towuti Kabupaten Luwu Timur, tidak semua Desa sesuai Undang-Undang RI Nomor 32 Tahun 2004 tentang Pemerintahan Daerah dan Peraturan Pemerintah Nomor 72 Tahun 2005 tentang Desa. Walaupun telah adanyaUndang-Undang yang baru yaitu Undang-Undang No. 6 Tahun 2014 tentang Desa, dan peraturan pemerintah No. 43 Tahun 2014 tengan Desa. Ketidak sesuaian tersebut ternyata dipengaruhi oleh beberapa faktor, yaitu faktor pendidikan, pekerjaan, dan pengelaman menjabat.